PHILOSOPHICAL PERSPECTIVE ON PLATO'S ALLEGORY OF THE CAVE - Umida Uzbekboyeva (Modern American Journals, 2025)
Plato's Allegory of the Cave serves as a profound philosophical metaphor that explores the nature of reality, perception, and enlightenment. This work examines the allegory's implications on human understanding and the journey from ignorance to knowledge. Through the depiction of prisoners who perceive shadows as reality, the allegory challenges readers to reflect on the limitations of their own perceptions and the importance of seeking deeper truths. This analysis highlights how the allegory remains relevant in contemporary discussions about knowledge, reality, and the impact of societal beliefs on individual understanding.
Keywords: Plato, Allegory of the Cave, Philosophy, Reality and Perception, Enlightenment, Shadows and Illusions, Education, Philosophical Allegory